PENERAPAN IPTEK USAHA PEMBUATAN TAHU DAN TEMPE DI BANDUNGAN KABUPATEN SEMARANG - Sunyoto, Sunyoto; Rosidah, Rosidah; Bintari, Siti Harnina (Universitas Negeri Semarang, 2014)
The purpose of this activity is to resolve the problems faced by the industry partner with the business of making tofu and tempeh, which is located in the village of Kenteng, Bandungan subdistrict, Semarang regency. As this activity involves the implementation team of lecturers with expertise appropriate to the needs of the field and assisted students. In the implementation used multiple methods of mutual support, with a practice emphasis directly by partners and mentoring activities. The results of these activities include 1) One unit of soybean grinding machine with an electric motor drive power 1 HP, 2) One unit of soybean crusher drive motor gasoline of 5.5 PK and has a production of capacity of 300 kg / hour, or five times that of soy-solving process manually which is only 60 kg / h, 3) Both the partners I and II have applied with better production management, and a cleaner production equipment, and workers had to use health and safety equipment. Impact activities include economic and non-economic aspects. The economic impact can be measured from the increased productivity and better product quality so as to increase the selling value of products. Non-economic impact can be measured from the comfort of work will also indirectly affect the economic benefits.